Turek's orthopaedics principles and their application - Weinstein, Stuart L.; Buckwalter, Joseph A.; Turek, Samuel L. (Lippincott Williams & Wilkins, 2005)
Now in its revised, updated Sixth Edition, this text provides residents and medical students with a broad overview of adult and pediatric orthopaedics. Major sections focus on general and regional disorders of the musculoskeletal system. This edition's chapters on regional disorders have separate adult and pediatric sections and include sports medicine information and reviews of anatomy. Coverage of each disorder includes more details on treatment and prognosis. This edition also provides expanded coverage of molecular orthopaedics, biomaterials, orthotics and prosthetics, diagnosis by physica